Does the Rhythmic Gymnastics Training Affect Serum Bone Resorption and Oxidative Stress Markers? - Pinar Tatlibal, Faruk Turgay, Onur Oral, Zeinab Rezaee (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Rhythmic gymnastics training (RGT) includes intensive anaerobic loads, therefore it may cause oxidative stress (OS) and then consequently might negatively affect bone metabolism and nitric oxide (NO) levels which is related to vasodilation and bone metabolism. This study investigated the effects of chronic RGT on the markers of serum bone metabolism, OS, and NO levels together, which is yet unclear. Materials and methods: 16 girls rhythmic gymnasts (athletic group, AG; 10.33 ± 1.79, years) and 13 controls (CG; 9.23 ± 1.00 years) participated in this study. Type 1 collagen carboxy-terminal cross-linked telopeptide (ICTP) as bone resorption marker (using ELISA method), alkaline phosphatase (ALP), parathyroid hormone (PTH), calcium (Ca), and growth hormone (GH) as bone metabolism markers; Total oxidant /antioxidant status ratio (TOS/TAS) as OS index (OSI) and NO levels; Troponin-I (Tn-I), and CK-MB levels, alanine aminotransferase (ALT), aspartate amino transferase (AST), creatine kinase (CK) as muscle injury markers; Some hematological parameters including hemogram were measured by standard methods. Results: Serum ICTP1 (p= 0.01) and GH (47.4 %) levels of AG were significantly higher than CG, whereas Ca level (p= 0.04) and body fat rate values was lower (p= 0.00). There is no significant difference between the groups for other parameters. Conclusions: The results suggest that RGT training did not significantly affect OS and NO levels that can cause anemia. But besides the increased GH levels, bone development can be affected negatively in child gymnasts due to the increased ICTP and decreased Ca levels. Thus, a calcium-rich diet and regular observation of bone metabolism markers are recommended.